Metagenomic next-generation sequencing for the clinical identification of spinal infection-associated pathogens - Shi, Tengfei; Lin, Yuhan; Zheng, Xuexin; Ruan, Hongliang; Zhang, Rui; Liu, Yinhuan; Xu, Shaohan; Wang, Huafeng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to evaluate the efficacy of metagenomic next-generation sequencing (mNGS) technology for identifying pathogens associated with spinal infection (SI).MethodsA retrospective analysis was conducted on clinical data from 193 patients with suspected SI between August 2020 and September 2024. Based on histopathological results, the patients were divided into the SI group (n=162) and the non-SI group (n=31). The diagnostic performance of mNGS technology was compared with that of laboratory examination, imaging examination, and microbial culture.ResultsAmong SI group, mNGS detected 135 pathogens in 77.78% (126/162) of the cases, including nine cases of multiple infections. One or more pathogens were detected using mNGS in 86 patients with SI and negative microbial cultures. Staphylococcus aureus (22.22%, n=30) and Mycobacterium tuberculosis (22.22%, n=30) were the major pathogens, while various rare pathogens such as anaerobes, Brucella, and Coxiella burnetii were also detected. For the 40 cases with positive results for both culture- and mNGS-based identification, high consistency (77.50%) was observed. Antibiotic use did not significantly affect the mNGS detection rate (P = 0.45). There was no significant difference in the positivity rate of mNGS between CT-guided needle biopsy (80.00%) and surgical sampling (77.17%) (P = 0.72). The sensitivity of mNGS (77.78%) was significantly higher than that of traditional microbial culture (27.16%), and the specificity was similar (90.32% vs. 96.77%). Although the sensitivities of erythrocyte sedimentation rate-based assay (91.36%), magnetic resonance imaging (88.27%), and C-reactive protein-based assay (87.65%) were better than those of mNGS, their specificities were generally low (20%-40%).ConclusionThe pathogens responsible for SI are complex and diverse. As a novel diagnostic method, mNGS exhibits a high sensitivity and extensive pathogen coverage for SI diagnosis. When combined with imaging and laboratory indicators, mNGS can significantly improve the accuracy of SI diagnosis and provide strong support for clinical treatment.